A Case of Inconspicuous Recurrent Herpes Labialis Mimicking Unilateral Angular Cheilitis - Mandasari, Masita; Astuti, Ambar Kusuma; Rahmayanti, Febrina (UI Scholars Hub, 2018)
Recurrent herpes labialis (RHL) is a common manifestation of herpes simplex virus (HSV) reactivation in immunocompetent individuals, whereas angular cheilitis is an inflammatory lesion occurring on one or both lip commissures and is induced by local and/or systemic conditions. We describe a case of RHL eruption on the corner of the mouth, easily mistaken as angular cheilitis. Case Report: A 21-year-old male presented to our dental hospital with a 3 day history of a painful, unilateral lesion on the left corner of his mouth. The lesion featured an erythematous base with a yellowish crust that extended outward. We diagnosed the lesion as RHL. We prescribed chlorhexidine solution and topical acyclovir to be applied onto the lesion. At 2 weeks follow-up, the lesion was resolved. An RHL lesion that erupts on the corner of the mouth may initially resemble angular cheilitis. However, the typical clinical presentation, history of recurrence, and the absence of predisposing factors for other lesions suggested an infection caused by HSV. Conclusion: RHL which occurred at one side of the mouth corner can be similar with unilateral AC. But, detailed history taking and clinical observation led to correct diagnosis and management.